Identifying Client Emotional Signatures: Development of a New Scale - Michelle Webster; Julie Fitness (Psychotherapy and Counselling Journal of Australia)
This article describes the development and refinement of the Annandale Emotional Signature Scale; a measure that was subsequently employed as part of a battery of tests to explore the validity of the constructs of abandonment and annihilation. The Annandale Emotional Signature Scale (AESS) was first developed and administered to undergraduate psychology students, followed by a group of practitioners who were aware of the abandonment and annihilation dimensions. Based on the results with these sample populations, the AESS scale was modified and administered to a clinical population. From these studies with three different samples, two highly reliable factors emerged from the AESS. The Abandon factor comprises items describing feelings of inadequacy, self-critical thinking, and pleasing behaviours that indicate anxiety and worry about over-responsibility and rejection by others. The Annihilate factor comprises items describing adverse and traumatic events from the past, as opposed to currently anxious feelings and self-critical thoughts. Overall, the results of these studies indicate that, in line with our initial clinical observations, two different dimensions in client profiles may be identified, each with their own characteristic signature of feelings, thoughts and behaviours, and childhood memories.